2014
DOI: 10.1159/000357940
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Referral to 12-Step Mutual Self-Help Groups by Treatment Professionals?

Abstract: Background/Aims: Twelve-step mutual self-help groups provide cost-effective support for recovery from substance misuse problems. Evidence suggests they are successful as an adjunct to formal treatment and that referral from clinicians is important in fostering engagement. Methods: This study surveyed substance misuse treatment professionals employed within two agencies in Birmingham (UK). Results: A total of 92 clinicians (79.3%) eligible to participate completed a questionnaire that explored their attitudes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…At a time of cuts to services, AA and NA are both free, widely available and recommended for the treatment of alcohol and substance misuse by the National Institute for Clinical Excellence (NICE, 2011;Public Health England, 2013). Yet studies have found only between 46% (Day et al, 2005) and 33% of practitioners (Wall et al, 2014) regularly consider referring patients/clients into 12-Step programmes. This relatively low referral rate is despite evidence that 12-Step involvement is predictive of both better engagement with professionals (Ferri et al, 2006) and improved abstinence rates (Pagano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At a time of cuts to services, AA and NA are both free, widely available and recommended for the treatment of alcohol and substance misuse by the National Institute for Clinical Excellence (NICE, 2011;Public Health England, 2013). Yet studies have found only between 46% (Day et al, 2005) and 33% of practitioners (Wall et al, 2014) regularly consider referring patients/clients into 12-Step programmes. This relatively low referral rate is despite evidence that 12-Step involvement is predictive of both better engagement with professionals (Ferri et al, 2006) and improved abstinence rates (Pagano et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Patients entering treatment were assigned to an addiction therapist (AT), half of whom had been trained in RAIR. Those not trained in RAIR provided their standard referral (SR), typically a recommendation to find and attend MHG meetings upon completing residential/intensive outpatient treatment, although referral practices vary [11]. Patents were pretested at baseline and followed-up six months later on measures of mutual-help group affiliation, substance use, and PTSD.…”
Section: Methodsmentioning
confidence: 99%
“…Social support provided by MHGs like Alcoholics Anonymous and other 12-step groups improves outcomes [6, 9], even for those with concurrent PTSD and SUD [10], and efforts to promote participation reduce continuing care costs [7]. Post-treatment referral to mutual-help groups has been described as “an effective, low-cost option” [8] but treatment providers vary in consistency and methods of referral [11].…”
Section: Introductionmentioning
confidence: 99%
“…Long term cohort studies show that people who actively participate in mutual aid are more likely to sustain their recovery, 23 Clinicians should be aware of the range of mutual aid groups available locally and how to access them. Level of clinician knowledge about Alcoholics Anonymous groups has been positively correlated with levels of referral, 24 and attending a meeting is an invaluable learning experience. Evidence from randomised controlled trials suggests that proactive efforts to engage patients with mutual aid groups increase attendance, particularly introducing the patient to a group member in advance of a meeting.…”
Section: Mutual Aid Facilitationmentioning
confidence: 99%